BENTUK SINONIMI SEBAGAI ANALISIS SEMANTIK TERHADAP BAHASA MELAYU DIALEK PONTIANAK - Dwi Kurniasih (Madah: Jurnal Bahasa dan Sastra, 2023)
This study aims to describe and describe the synonymous forms of the Pontianak Malay dialect in Pontianak City using semantic analysis. This research uses descriptive qualitative method. Data collection techniques in this study used observation, recording, and listening to tapping. The data obtained in this study are in the form of synonyms in Pontianak Malay dialect. Based on the analysis of the data obtained from the research process found synonymy forms in the form of (1) absolute synonyms (2) proportional synonyms (3) near-synonyms